Związki rodzinne w polityce personalnej Justyniana I - Wolińska, Teresa (Acta Universitatis Lodziensis. Folia Historica, 2000)
In the article the author analyses the influence of family connections on the personal policy of Byzantine Emperor Justinian I (527-565). The author is trying to answer the extent to which his policy was determined by family solidarity and whether it could be called nepotism or not. The first part of the article is devoted to the settlement of the circle of people connected with the Emperor and his wife, Empress Theodora. It was not a large group of people, especially the family of Theodora was very small and almost unknown. Her father died when she was a child, she did not have brothers. We know only about the vicissitudes of one of her sisters, Komito. Justinian’s family is known better, because when his uncle Justin became Emperor, Byzantine historians were interested in his origin and family connections. In spite of that, in case of some persons it is impossible to determine the relation between them and Emperor Justinian (Germanus is a good example). The second part of the article is devoted to Justinian’s personal policy in relation to his family relationships. Upon the analysis of the Imperial family members’ career, the author concludes that generally speaking Justinian’s policy was not deprived of some elements of nepotism, yet this nepotism had very limited character and did not undermine state affairs. Social promotion of the Emperor’s family took place during his uncle’s reign, so he himself was not forced to support its members in a very offensive way. They generally possessed big properties and were rich, their wealth not being directly connected with the post they held. The fact of being a member of the Imperial family could have facilitated their career, but did not guarantee it automatically. In the case of Theodora’s family the situation was slightly differrent, as its membres descended indeed from the lowest part of the social ladder, yet the lack of male family membres made the only profit they could take out of it was just a good marriage. –However would Justinian support his relatives, he always considered their abilities first. That was one of the reasons why he never appointed his relatives to posts in the civil administration – their career was of military character. Almost all of Justinian’s collaborators were competent and skillful. The same can be said of the members of the Imperial family who played an important role in the army and court. The only exception we know was Areobindus, who showed indolence as a military commander in Africa. In comparison with the career of the persons not related to Justinian or Theodora, like Belisarius or Salomon of Dara, the members of the Imperial family did not distinguish themselves in any particular way. In spite of what has been said above, many people found entering the family (e.g. by marriage) very attractive. Those lucky to do so had already been high ranking people of the country, so the fact of becoming a member of the Imperial family could only make their position even stronger.